2021
DOI: 10.1002/suco.202100065
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on seismic performance levels of highly corroded reinforced concrete columns

Abstract: In the literature, only one empirical model is available as a nondestructive method for the prediction of seismic performance levels of corroded reinforced concrete (RC) columns as a function of the initial corrosion crack width at lower corrosion levels. Because of the ruptured transverse reinforcement bars at higher corrosion levels, the structural behavior may turn brittle in terms of shear failure. Therefore, in this study, higher corrosion levels for a different concrete strength level from that empirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…𝐷 𝑒𝑡 𝜃 displacement and plastic rotation corresponding to CL=0. which has been also reported in the literature [44]. This trend is not perceived under Friuli accelerogram (Fig.…”
Section: Figure 9 -Lateral Displacement Responses Under Artif1supporting
confidence: 87%
“…𝐷 𝑒𝑡 𝜃 displacement and plastic rotation corresponding to CL=0. which has been also reported in the literature [44]. This trend is not perceived under Friuli accelerogram (Fig.…”
Section: Figure 9 -Lateral Displacement Responses Under Artif1supporting
confidence: 87%
“…It can be derived that reinforcement corrosion should have detrimental impact on seismic performance of RC structures. Therefore, experimental studies of corroded RC columns were abundantly conducted during the past few years since they provide easier and more direct investigations on the structural behavior of corroded RC buildings (Dai et al 2021;Meda et al 2014;Ma et al 2012;Yalciner and Kumbasaroglu 2020;Celik et al 2022;Rajput and Sharma 2018;Guo et al 2015;Yuan et al 2018;Deng et al 2022;Ma et al 2018;Zhou et al 2020;Zhao et al 2021;Koçer et al 2021;Yang et al 2016;Chang et al 2020;Rinaldi et al 2022;Li et al 2018;Goksu and Ilki 2016). For instance, Meda et al (2014) performed cyclic loading tests on two full-scale column specimens to investigate the influence of corrosion on the structural behavior, and revealed that corrosion of rebars causes a significant reduction in the structural ductility.…”
Section: Introductionmentioning
confidence: 99%
“…As revealed in the abovementioned test results, with the increase of axial load, the failure mode of corroded columns changed with the decreased ductility and energy dissipation. The axial compression ratio of columns in many existing buildings constructed before the issue and adoption of seismic design code often exceeds 0.6 or even much larger due to the use of lowstrength concrete (Celik et al 2022;Huan et al 2020;Bru et al 2018). However, in previous experimental researches, most of the corroded RC columns were designed with low axial compression ratio, e.g., 0.1 in Guo et al (2015), 0.13 in and Rinaldi et al (2022), 0.17 in Zhou et al (2020) and 0.2 in Goksu et al (2016).…”
Section: Introductionmentioning
confidence: 99%